Principles of the law of contract in Malaysia, 3rd edition - Abdurrahman, Syed Ahmad Shihabuddin (LexisNexis, 2010)
This book is primarily meant for students studying the law of contract in Malaysia. It also caters to students of law, accountancy, engineering and business administration in helping them understand the basic principles of the law of contract. The provisions of the Contracts Act 1950 are well explained along with illustrated examples of contractual situations based on decided cases. The application of Syariah law in dealing with contract cases is also discussed in detail.